Issues Of Patriotic Education In Uzbek Folk Tales - Abdullayeva Barno Sayfutdinonovna; Xudoyberganova Matluba Qulsoxatovna (Genius Journals, 2023)
This article discusses the meaning and essence of the formation of patriotism in our youth through Uzbek folk tales.
Keywords: Fairy tale; folk tale; folklore